Pelatihan Penyusunan Rencana Pelaksanaan Pembelajaran Model 1 Lembar Versi Menteri Nadiem bagi Guru Sekolah Dasar - Sabina Ndiung; Sebastianus Menggo; Mariana Jediut; Eliterius Sennen; Arnoldus Helmon (Jurnal Pengabdian Pada Masyarakat, 2020)
TRAINING FOR CONSTRUCTING OF THE MINISTER NADIEM’S VERSION OF ONE-SHEET LESSON PLAN FOR ELEMENTARY SCHOOL TEACHERS. Learning planning is a system that refers to the objective to be achieved because it is the basis of work in carrying out all activities in learning. A system is a unit consisting of a number of components that are interconnected and interact with one another in an effort to achieve the goal. At present, elementary school teachers have difficulty in conducting the Minister Nadiem’s new policy as stipulated in a circular letter No. 14 of 2019 concerning the simplification of the administration of learning, especially related to the implementation of lesson plan of the 2013 curriculum becomes one-sheet lesson plan model. Simplifying the components of the 2013 curriculum learning lesson plan to adapt the model developed by Glaser which is the basic model in constructing lesson plan with the scope of its components, namely objective, learning procedure, and assessment. Thus, this training focuses on mentoring for teachers in developing a one-sheet lesson plan in accordance with the needs of SDN Ules, South Lembor sub-district, West Manggarai regency which is oriented toward increasing teacher creativity and innovation in learning. This training includes four stages, namely (1) needs analysis of the participants (teachers) of the training activities; (2) workshop on constructing of one-sheet lesson plan of the Minister Nadiem’s version; (3) construction and presentation of activities result, and (4) evaluation. The outcome of this activity is the availability of lesson plan model which is ready to be used by teachers in the learning process of academic year of 2020/2021, equipped with portfolio and project assessment guidelines according to subject to achieve meaningful learning goals.